141k views
4 votes
Lloyd solves the equation 24x + 18(x - 2) = 216 for x. Some of his steps are shown.

Step 1: 24x + 18(x - 2) = 216

Step 2: 24x + 18x - 36 = 216

Step 3: 42x - 36 = 216

Step 4: 42x = 252

a:combined like terms
b:used the distributive property
c:used the addition property equality
d:used the multiplicative inverse of property

User Cyrus Zei
by
5.1k points

1 Answer

3 votes

Answer:

Explanation:

6,498.123

User Akash Nayak
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.